1986
DOI: 10.1177/00220345860650090801
|View full text |Cite
|
Sign up to set email alerts
|

Root Caries in an Optimally Fluoridated and a High-fluoride Community

Abstract: The purpose of this study was to measure the prevalence and distribution of root caries in two New Mexico communities. One community, Deming, had a natural fluoride concentration of 0.7 mg/L in its drinking water, optimum for its climate. The other, Lordsburg, was naturally fluoridated at 3.5 mg/L, five times the optimum. Dental examinations were carried out on 151 adults in Deming (mean age, 39.8 years) and 164 in Lordsburg (mean age, 43.2 years); only persons born in the communities were included. Prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 16 publications
4
60
1
Order By: Relevance
“…Even though observational cohort studies such as the FDCS do have less inferential power than randomized controlled clinical trials, they nonetheless offer the important advantages of using a sample that is representative of a defined population, they include persons regardless of whether they actually seek dental care, and they monitor change due to dental care that is provided in 'realworld' private practice settings where the overwhelming majority of dental care is delivered [Guess et al, 1995;Gilbert et al, 1998a]. We also remind the reader that subgingival root surfaces were not assessed for root caries, which may have caused an underestimate of root caries incidence [Burt et al, 1986;Locker et al, 1989;Katz, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Even though observational cohort studies such as the FDCS do have less inferential power than randomized controlled clinical trials, they nonetheless offer the important advantages of using a sample that is representative of a defined population, they include persons regardless of whether they actually seek dental care, and they monitor change due to dental care that is provided in 'realworld' private practice settings where the overwhelming majority of dental care is delivered [Guess et al, 1995;Gilbert et al, 1998a]. We also remind the reader that subgingival root surfaces were not assessed for root caries, which may have caused an underestimate of root caries incidence [Burt et al, 1986;Locker et al, 1989;Katz, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Several human studies showed fewer root carious lesions in adults benefiting from fluoridated water supplies [Brustman, 1986;Burt et al, 1986;Hunt et al, 1989;Locker et al, 1989]. Interestingly, Stamm et al [1990] investigated that lifelong residents of a fluoridated (1.6 ppm) community in Ontario, Canada, had 77% less root caries compared to lifelong residents of a nearby unfluoridated community (0.2 ppm).…”
Section: Use Of Dentifrices Containing Fluoride For the Management Ofmentioning
confidence: 99%
“…Moreover, the access to approximal RCLs for restorative management is limited or requires extensive removal of sound dental hard tissues. Therefore, several approaches to prevent initiation (Burt et al 1986;Mojon et al 1998;Tan et al 2010) or inactivate RCLs (Papas et al 2007;Ekstrand et al 2013) have been proposed.…”
Section: Introductionmentioning
confidence: 99%